Effectiveness of the CERIA Flipbook on Elementary Students’ Disaster Literacy and Conceptual Understanding: A Research and Development Study - Adinda Nurul Annisa; Julia; Ali Ismail (International Journal of Education and Humanities, 2026)
Elementary science learning on volcanic eruption topics remains challenging for students. This difficulty arises from the abstract nature of the content and the limited use of interactive visual media, which often leads to low conceptual understanding. This study aims to develop and evaluate the CERIA flipbook (Creative Education with Augmented Reality for Science) as an AR-based learning medium that integrates contextual elements from students’ daily environments to support meaningful learning. The study employed a Research and Development (R&D) approach using the ADDIE model and implemented a one-group pretest–posttest design involving 25 fifth-grade students at SD Negeri Kodasari I, Majalengka, Indonesia. Data were collected through expert validation sheets, essay-based pretest and posttest, and student response questionnaires, and were analyzed using descriptive, quantitative, and inferential techniques. The results indicate that the media is highly feasible, with validation scores of 90.83% from media experts and 94.44% from content experts. Students’ conceptual understanding improved significantly, as reflected in the increase of mean scores from 41.8 to 82.64 (p < 0.001), with an N-Gain score of 0.73, categorized as high. In addition, students showed very positive responses toward the media, with an average score of 91.25%. These findings contribute to the growing evidence on the integration of contextual elements into AR-based science learning and offer a replicable pedagogical model for enhancing disaster literacy in elementary education